Incident and Service Request Management for Academic Information System based on COBIT - Indra Kharisma Raharjana; Ibnu Ibadillah; Purbandini Purbandini; Eva Hariyanti (IAES Indonesia Section, 2018)
This paper explores application of Incident and Service Request Management for academic services. We are using Control Objectives for Information and Related Technologies (COBIT) framework as basis for determining the activities in Incident and Service Request Management. The COBIT itself is an IT governance framework included incident handling and service requests, also providing incident response and service request decisions. The software will be developed as a proof of concept that it brings benefits to academic service operations. For most academic services in university, encountered a problem such as incidents reports or a request for services are not immediately addressed, took a long time to respond, or even lost and left unreadable. It is a good idea to standardize incident management and plant it into academic information systems to enforce its application. In software development, we perform five development stages: requirement analysis, system design, stakeholder confirmation, system development, and system evaluation. In requirement analysis stages, we elicited features from activity describe in COBIT and customize it based on interviews and observation. We design use case diagram, use case scenario and database design in system design stages. In stakeholder confirmation stages, a meeting with the stakeholders held and discuss whether the system complies with the requirements or not. system adaptations are made to answer stakeholders concern. System development is conducted based on confirmed system design. Stakeholder evaluated after they follow the case simulation session. Stakeholders provide an evaluation of the system according to their role, based on their experience when using the system in the simulation session. User experience (UX) aspects are also evaluated based on user's interaction with the system. User experience results obtained meet all aspects, including useful, usable, desirable, findable, accessible, credible, and valuable. The evalu.